2011
DOI: 10.2298/sarh1108439t
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue thickness of face profile conditioning by dento-skeletal anomalies

Abstract: The thickness of facial soft tissue considerably influences facial profile appearance in persons with a dento-skeletal anomaly. Not only do soft tissues adapt to the existing jaws relationship, but can also camouflage present anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In the present study, the finding in the group of patients with a skeletal jaw relationship in Class II/2 showed that men had a significantly increased FSTT of the subnasal area, sulcus labrale superius, labrale superius and labrale inferius, and area of the chin compared women ( Table 6 ). According to previously published research by Tanic et al, who compared FSTT using the same method as in the current study, they established that the thickest soft tissues in the area of the sulcus of the upper lip, upper and lower lip, showed significant differences between men and women [ 25 ]. In a further study by same authors, published a year later, they established significant differences in the area of the sulcus labrale superius and labrale inferius, with patients in Class II/2 having much greater values of FSTT compared with patients in Class II/1 [ 26 ].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In the present study, the finding in the group of patients with a skeletal jaw relationship in Class II/2 showed that men had a significantly increased FSTT of the subnasal area, sulcus labrale superius, labrale superius and labrale inferius, and area of the chin compared women ( Table 6 ). According to previously published research by Tanic et al, who compared FSTT using the same method as in the current study, they established that the thickest soft tissues in the area of the sulcus of the upper lip, upper and lower lip, showed significant differences between men and women [ 25 ]. In a further study by same authors, published a year later, they established significant differences in the area of the sulcus labrale superius and labrale inferius, with patients in Class II/2 having much greater values of FSTT compared with patients in Class II/1 [ 26 ].…”
Section: Discussionmentioning
confidence: 87%
“…Jabbar et al determined the existence of reduced thickness of soft tissue in the chin area in patients in Class III in comparison with other classes, without significant sex differences [ 9 ], which is similar to the results of this study. Other studies have also emphasized reduced FSTT in the chin area, and an increase in FSTT in the area of the upper lip and upper lip sulcus as compensation for the existing skeletal disharmony in Class III [ 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive circumstance is that, in some analyses, statistical significance was not established, which points to two possible answers: 1) irregularity in certain segments of a dento-skeletal profile is less pronounced [ 7 ] and, 2) thickness of soft tissues of lips in class II division 2 is increased so that it camouflages a characteristic dento-skeletal profile form. Almost all the authors who have examined this issue agree with the second statement, since they established that soft tissues of a face, with its fullness, can act in two ways: if the face is thin, it emphasizes the listed marks of the existing malocclusion, or if the face is of a fuller-compensatory appearance, it masks the existing skeletal relationship [ 7 , 17 , 18 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soft-tissue profile in persons with class II division 2 is also specific, and described as a profile of “sharp” facial contours [ 17 ]; with concave lower third of the face with a protruding nose and tip of the chin, thin vermillion, and retruded lips ( Figure 2 ) [ 10 , 11 , 18 ]. The rima oris is placed high, so that when smiling, the upper alveolar arch covered with the gingiva is first displayed (gummy smile) [ 19 – 23 ].…”
Section: Introductionmentioning
confidence: 99%